Implementasi Prinsip Kehati-Hatian Dan Sistem Tanggung Renteng Dalam Meminimalisir Pembiayaan Bermasalah Pada Bank Wakaf Mikro Tebuireng Mitra Sejahtera Jombang - Annis, Syafrin Aulia; Mutafarida, Binti; Sugiarto, Suprihantosa; Yuliani, Yuliani (Program Studi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2024)
This article aims to determine the implementation of the prudential principle and joint responsibility system in minimising problematic financing at BWM Tebuireng Mitra Sejahtera. This research uses a qualitative approach with descriptive research. The data collection techniques used were observation, interview, and documentation. The results of this study explain that 1) The implementation of the prudential principle at BWM Tebuireng Mitra Sejahtera has been implemented properly and effectively according to the stages and procedures that have been determined through the application of the 5C principle assessment (Character, Capacity, Capital, Collateral, and Condition of Economy). Of the five principles, the most prioritised assessment by BWM Tebuireng Mitra Sejahtera is the Character of prospective customers in analysing the feasibility of prospective customers. 2) The implementation of the joint responsibility system is carried out through several stages, among others: Identification, Socialisation, Customer Eligibility Test, Pre PWK (Pre Mandatory Group Training), PWK (Mandatory Group Training), and Halmi (Weekly Halaqah). 3) The implementation of the prudential principle and joint responsibility system can minimise the number of non-performing financing at BWM Tebuireng Mitra Sejahtera marked by the percentage of NPF (Non Performing Financing) which has decreased every year.